Current Status of Molecular Targeted Therapies in Hepatocellular Carcinoma - Suh, Sang Jun; Yim, Hyung Joon (The Korean journal of gastroenterology, 2013)
Hepatocellular carcinoma (HCC) is one of the leading causes of cancer death in Korea. Curative treatment is only possible when the disease is diagnosed at the early stage. The prognosis of patients with HCC is even dismal in advanced stages. No systemic cytotoxic chemotherapy has proven to be beneficial in overall survival. Recently, the understanding of the molecular pathogenesis led to the development of new therapies. With the evidence of dysregulation of critical genes associated with cellular proliferation, growth factor signaling, cell cycling, apoptosis, and angiogenesis in HCC, a number of molecular target agents are under clinical trials. Sorafenib is the first systemic anticancer drug which has proven to gain survival benefit in the global as well as Asia-Pacific trials. However, the survival gain is still modest, and further efforts to improve outcomes in patients with HCC are necessary by developing novel drugs or combining other forms of therapies. This article will review signaling pathways in HCC and introduce molecular target agents under investigation currently.Hepatocellular carcinoma (HCC) is one of the leading causes of cancer death in Korea. Curative treatment is only possible when the disease is diagnosed at the early stage. The prognosis of patients with HCC is even dismal in advanced stages. No systemic cytotoxic chemotherapy has proven to be beneficial in overall survival. Recently, the understanding of the molecular pathogenesis led to the development of new therapies. With the evidence of dysregulation of critical genes associated with cellular proliferation, growth factor signaling, cell cycling, apoptosis, and angiogenesis in HCC, a number of molecular target agents are under clinical trials. Sorafenib is the first systemic anticancer drug which has proven to gain survival benefit in the global as well as Asia-Pacific trials. However, the survival gain is still modest, and further efforts to improve outcomes in patients with HCC are necessary by developing novel drugs or combining other forms of therapies. This article will review signaling pathways in HCC and introduce molecular target agents under investigation currently.